Is there philosophy before the greek? - Mesquita, António Pedro (Revista Archai, 2025)
To circumscribe, in a strict and consensual way, that which is conventionally called “Ancient Philoso-phy” is not a task that poses difficulties.If this concept is addressed from an historical point of view, one is at once put before a certain time frame, taking place approximately between the VII century B.C. and the VI A.D., which mediates the emergency of the first philosophi-cally shaped speculation, with Thales of Miletus, and the last testimonies of a specifically Greek or “pagan” thought, with the neoplatonism, within which it is possible to recognize a sequence of specific periods, stages and epochs, as well as the flourishing of as many schools and currents of thought, structuring and filling out Ancient Philosophy.However, what is thus exposed is no more than Ancient Philosophy as an historiographical concept or, if preferred, as the history of Ancient Philosophy: and as historiographical concept, Ancient Philosophy can be depicted in those terms, converging into a large periodization block, respected and acknowledged by all.Nevertheless, if one can accept a consensus on the historical delimitation of Ancient Philosophy, the same does not happen with its philosophical characterization. And, in the second case, such a consensus is absent because, first and foremost, there is a lack of consensus regarding the preliminary thesis according to which, in addition to historical description, Ancient Philosophy can also be put under philosophical perspective, that is, the thesis according to which, far from being just an historical-philosophical period, Ancient Philosophy amounts, before anything else, to a particular mode of consciousness, the recognizance of which would precisely constitute the alluded philosophical characterization of the concept of Ancient Philosophy. This paper follows this second direction. Hopefully, in doing so, the answer to the question put forward in the title – “Is there philosophy before the Greeks?” – will impose itself by itself